Performance characterization and radiation tolerance evaluation of the SSA2 ASIC, the strip sensor readout ASIC of the CMS Outer Tracker at the HL-LHC. (1st January 2023) - Caratelli, A.; Bergamin, G.; Ceresa, D.; Kaplon, J.; Kloukinas, K.; Nedergaard, C.; Nookala, A.; Scarfi, S.
Abstract: This contribution presents the results of the performance characterization and radiation tolerance evaluation of the SSA2 ASIC, the short-strip readout ASIC for the CMS Outer-Tracker PS-module. The ASIC performance is characterised by different temperatures and operating conditions, at the die level as well as at the wafer level. The radiation evaluation comprises Total-Ionising-Dose (TID) tests and Single-Event-Effects (SEEs). Wafer-level testing provided a large dataset to evaluate the production yield. The presented test results are in agreement with the design simulations and are well within the application requirements for operation in the CMS outer-tracker at the HL-LHC.